Exploring the Role of Facilities in Guidance and Counseling Services in Schools: A Comprehensive Review - Cania, Lita Fitara; Ahmad, Riska; Syukur, Yarmis (Jurnal Bimbingan dan Konseling Terapan, 2024)
This paper explores the critical importance of guidance and counseling facilities in schools for optimal service delivery. With schools often overlooking the necessity of these facilities, it is imperative to shed light on the consequential deficiency in the delivery of such services, negatively impacting the academic trajectory and life skills development of students. The literature review methodology employed in this study delves into the conceptualization of guidance and counseling, the essential resources required, and the significant role of school administrators and BK (guidance and counseling) teachers in ensuring these facilities are available. The findings reveal the paramount importance of data collection instruments, data storage devices, service delivery tools, and BK room equipment for effective guidance and counseling. Furthermore, this study underscores the legislative mandates calling for the provision of these resources. Ultimately, this paper argues that optimal facilities, strategic planning, and collaboration between all school personnel are key to the successful implementation of guidance and counseling services in schools. The insights derived from this research are beneficial for school administrators, BK teachers, and policymakers, contributing to the enhancement of educational outcomes and the overall student experience.